Implementation Human Rights Values Man for Avoid Behavior Bullying (Bullying) on Students Elementary School - Yuni, Isma (International Journal of Students Education, 2024)
This study aiming for give better understanding deep about draft bullying, especially in context environment schools in Indonesia as well as how method overcome it. The method used in this study that is method review literature systematic (systematic literature review) with to browse as many as 10 articles and the official website that has published in accordance with theme this study. Research results give understanding about benefits and objectives prevention bullying in the environment school through implementation of Citizenship Education ( PKn ) for strengthen rights and obligations child as well as to plant Human Rights Values Humans so that children can appreciate and respect the rights of others, as well as the role of teachers and institutions education in countermeasures case bullying that still exists often occurs in the environment school.